2018
DOI: 10.3389/fonc.2018.00208
|View full text |Cite
|
Sign up to set email alerts
|

Management of Brain Metastases in Epidermal Growth Factor Receptor Mutant Non-Small-Cell Lung Cancer

Abstract: Lung cancer remains a leading cause of mortality with 1.69 million deaths worldwide. Activating mutations in epidermal growth factor receptor (EGFR), predominantly exon 19 deletions and exon 21 L858R mutations, are known oncogenic drivers identified in 20–40% of non-small-cell lung cancers (NSCLC). 70% of EGFR-mutant NSCLC patients develop brain metastases (BM), compared to 38% in EGFR wild-type patients. First-generation tyrosine kinase inhibitors (TKIs), such as erlotinib and gefitinib have proven to be supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 91 publications
0
60
0
Order By: Relevance
“…A number of studies indicated the efficacy of EGFR TKI treatment against NSCLC BMs (1,26,42). The results from the LUX-Lung 2/3/6 trials (9,20,21) indicate that afatinib can be used as first-line treatment of metastatic NSCLC with non-resistant EGFR mutation including L861Q/G719X/S768I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies indicated the efficacy of EGFR TKI treatment against NSCLC BMs (1,26,42). The results from the LUX-Lung 2/3/6 trials (9,20,21) indicate that afatinib can be used as first-line treatment of metastatic NSCLC with non-resistant EGFR mutation including L861Q/G719X/S768I.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that EGFR mutation patterns in NSCLC primary lesions and metastases in various body locations are not consistent with that found in the BMs (24)(25)(26), possibly because of the specific events required for cancer cell migration to and survival in the brain. Indeed, a primary tumor is composed of various clones (27,28) and not all of them will have the abilities to spread in circulation, cross the BBB, survive in the brain microenvironment, and invade the brain tissue (1,29).…”
Section: Introductionmentioning
confidence: 97%
“…Importantly, these mutations also play a significant role in various treatment options, including tyrosine kinase inhibitors and monoclonal antibodies targeting EGFR, HER2, or both [153], as well as for imaging. Especially the evaluation of a response to these targeted therapy options in patients with brain metastases (from melanoma, lung, or breast cancer) as well as in glioma patients is the indication with the highest clinical potential for EGFR-and HER2-targeted PET [154,155]. In recent years, radiolabeled EGFR and HER2 antibodies, as well as tyrosine kinase inhibitors, have been used as PET imaging agents.…”
Section: Pet Imaging Of the Epidermal Growth Factor Receptor Familymentioning
confidence: 99%
“…Hippocampal-sparing WBRT reduces the radiation exposure of the hippocampus while preserving the therapeutic benefit on the grounds that the hippocampus has a low frequency of brain metastasis occurrences, while WBRT-induced hippocampal damage is frequently associated with neurotoxicity. 56 The neurodegenerative effects of WBRT have also incited effort to reduce the exposure of the brain to radiation via the expansion of SRS to patients with greater numbers of brain metastases in place of WBRT. 56 Responses of NSCLC brain metastases to radiation therapy have been shown to improve when radiation therapy is combined with immune checkpoint inhibitors (ICIs).…”
Section: Definitive Treatments For Brain Metastasesmentioning
confidence: 99%
“…56 The neurodegenerative effects of WBRT have also incited effort to reduce the exposure of the brain to radiation via the expansion of SRS to patients with greater numbers of brain metastases in place of WBRT. 56 Responses of NSCLC brain metastases to radiation therapy have been shown to improve when radiation therapy is combined with immune checkpoint inhibitors (ICIs). The primary ICIs investigated in NSCLC are the anti-programmed cell death protein 1 (anti-PD-1) monoclonal antibodies nivolumab and pembrolizumab, and the anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) monoclonal antibody ipilimumab.…”
Section: Definitive Treatments For Brain Metastasesmentioning
confidence: 99%